PENGARUH NILAI PELANGGAN, PERSEPSI HARGA, CITRA PERUSAHAAN, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI PLN AREA SURAKARTA - -, Ayu Kusuma Galuh Candra Kirana (Universitas Slamet Riyadi, 2015)
This research is conducted to know the significancy between: The customer value, price perceived, corporate image and service quality to customer satisfaction in Electricity Public Service Surakarta Area. The population is industry and business customer of Electricity Public Service Area Surakarta as many as 473 customer. The technique of gathering the data is using inquiry sheet through validity test and reiability test. The analysis technique uses double regression with classical assumption. The analysis result shows: (1) The regressionâ€s equation is Y = -3,227 + 0,55 2X1 + 0,025 X2 + 0,087 X3 + 0,139 X4. (2) The t test variable of customer value and service quality the significancy less than 0,05 so the free variables are significant effect to customer satisfaction. The t test variable of price perceived and corporate image the significancy more than 0,05 so the free variables are not significant effect to customer satisfaction. F test the significancy less than 0,05 it could be concluded that the data is significant. Coeffisien determination test is R2 = 0,764 it means that customer value, price perceived, corporate image and service quality are explain as 76,4% of the customer satisfaction Electricitty Public Service Surakarta Area, futher more influenced by the other variables. Keywords: customer value, price perceived, corporate image, service quality, customer Satisfaction